Propulsion Systems - Serpi, Alessandro; Porru, Mario (IntechOpen, 2019)
The transport sector is one of the most valuable sectors in the world. It represents the large oil consumers but still relies mainly on fossil fuels. Since the world trend in fossil fuel use is expected to increase further, a more sustainable transportation system is unavoidable to cope with emerging economic and social issues, such as massive energy consumption and emissions of pollutant gases. In this regard, this book provides an overview of some recent and promising technological advancements in propulsion systems, ranging from on-board components to different propulsion system architectures. In particular, the book aims at giving a brief but significant insight into propulsion system design and architecture, by covering different topics and application fields (road, marine, and aerospace).